THE CONSTRUCTION OF A TRANSPORT PUZZLE ON THE EXAMPLE OF INTERNATIONAL TRADE (Socio-economic relations in the digital society, 2019)
The twenty-first century is the time of the informational era, the time when information, technology and capital guide the world. Along with these modern trends in the development of society, agriculture is of paramount importance. This applies to economically backward countries and advanced countries. The urgent task for the development of agriculture is the rational use of raw materials and materials; Drafting an optimal plan for transportation of agricultural products, inventory management and reducing the cost of its transportation. The article demonstrates the use of linear programming to determine the optimal transportation plan between different countries. On the example of the international trading transaction for grain transportation the minimal cost was calculated and the optimal plan of transportation was drawn up.
Keywords: linear programming; transport task; target function; optimal plan; cost matrix